Investigating the Role of the NLRP3 Inflammasome Pathway in Acute Intestinal Inflammation: Use of THP-1 Knockout Cell Lines in an Advanced Triple Culture Model - Busch, Mathias; Ramachandran, Haribaskar; Wahle, Tina; Rossi, Andrea; Schins, Roel P. F. (Frontiers in Immunology, 2022)
The NLRP3 inflammasome plays an important role in intestinal homeostasis as well as inflammation. However, in vivo studies investigating the role of the NLRP3 inflammasome in inflammatory bowel disease (IBD) report contrasting results, leaving it unclear if the NLRP3 inflammasome augments or attenuates intestinal inflammation. To investigate the role of the NLRP3/caspase-1 pathway in a model of acute intestinal inflammation, we modified a previously established in vitro triple culture model of the healthy and inflamed intestine (Caco-2/HT29-MTX-E12/THP-1). Using THP-1 knockout cell lines, we analyzed how the NLRP3 inflammasome and its downstream enzyme caspase-1 (CASP1) affect inflammatory parameters including barrier integrity and cytotoxicity, as well as gene expression and secretion of pro-inflammatory cytokines and mucus. Furthermore, we investigated differences in inflammation-mediated cytotoxicity towards enterocyte-like (Caco-2) or goblet-like (HT29-MTX-E12) epithelial cells. As a complementary approach, inflammation-related cytotoxicity was analyzed in intestinal tissue explants from wildtype (WT) and Nlrp3-/- mice. Induction of intestinal inflammation impaired the barrier, caused cytotoxicity, and altered gene expression of pro-inflammatory cytokines and mucins in vitro, while the knockout of NLRP3 and CASP1 in THP 1 cells led to attenuation of these inflammatory parameters. The knockout of CASP1 tended to show a slightly stronger attenuating effect compared to the NLRP3 knockout model. We also found that the inflammation-mediated death of goblet-like cells is NLRP3/caspase-1 dependent. Furthermore, inflammation-related cytotoxicity was present in ileal tissue explants from WT, but not Nlrp3-/- mice. The here presented observations indicate a pro-inflammatory and adverse role of the NLRP3 inflammasome in macrophages during acute intestinal inflammation.